1/n*(n+x)=1/x*[1/n-1/(n+x)]
(1)1/2+1/6+1/12+1/20+1/30+1/42+1/56+1/72+1/90
=1-1/2+1/2-1/3+1/3-1/4+……+1/9-1/10
=1-1/10
=9/10
(2) 1/1*4+1/4*7+1/7*10+1/10*13+1/13*16
=1/3*(1-1/4+1/4-1/7+1/7-1/10+1/10-1/13+1/13-1/16)
=1/3*(1-1/16)
=1/3*15/16
=5/16
1/2+1/6+1/12+1/20+1/30+1/42+1/56+1/72+1/90=9/10
1.1/n*(n+x)=1/x*(1/n-1/n+x)
2.
(1):原式=1/1*2+1/2*3+1/3*4+1/4*5+1/5*6+1/6*7+1/7*8+1/8*9+1/9*10
=1-1/10
=9/10
(2):原式=1/3*(1-1/4+1/4-1/7+1/7-1/10+1/10-1/13+1/13-1/16)
=1/3*(1-1/16)
=15/16
1、 原始=1/2+1/2-1/3+1/3-1/4+。。。。。+1/9-1/10=1-1/10=9/10
2、 1/1*4=1/3*(1-1/4)
原始=1/3*(1-1/4+1/4-1/7+。。。。。+1/13-1/16)=1/3*(1-1/16)=1/3*15/16=5/16